IMMERSIVE UPPER ARMS GAMES REHABILITATION FOR STROKE SURVIVOR - Mohd Noor, Nur Amiera (IRC, 2020)
Stroke cases have been increasing rapidly all over the world either in Asia, Europe, America, or Australia. In Malaysia, every year, there is around 50 000 new cases are reported. About half of the people affected by stroke are in working age and over half of the stroke, survivor suffers from a disability which affected their performance in performing daily life activity. Thus, to improve patient quality of life, rehabilitation is needed for them to relearn all the skills that they have acquired before the stroke. This paper would propose an interactive version of current stroke rehabilitation to help stroke patients to practice all the exercise using virtual reality. Since rehabilitation required a lot of repetitive movement, patient enthusiasm might reduce according to time which can lead to demotivation to attend all the rehabilitation tasks. This research needs to study virtual reality rehabilitation able to motivate patients in undergoing their rehabilitation. Virtual reality rehabilitation is the compensate method used together with conventional rehabilitation method to increase the progress made by the patient. Nowadays, there are a lot of virtual reality games in the market which can be used by patient. However, some of the games are not suitable for stroke patient as they have a movement limitation especially in upper arms parts. To conduct the preliminary studies, literature review regarding the project and specifying user will be done. Rapid Application Development (RAD) method will be implemented for the system development life cycle (SDLC) methodology for system development. This project focus on patient who almost has a functioning arms movement. Patients need to be able to move their hands to play the games and patient rehabilitation are focusing to train their upper arms. Several modules of games are being created to ensure that patients can play this game for their rehabilitation. Assessment module is played to ensure that patient can move their upper arms while bowling module is used to train patient arms by swing their arms while hitting the bowling pin. The result is measure by the acceptance by the therapist to ensure this game is suitable for their patient to train their upper arms.